1984
DOI: 10.1177/002199838401800304
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Model for the Growth of Matrix Cracks in Composite Laminates

Abstract: This paper presents a stochastic simulation model for the growth of multiple matrix cracks in composite laminates subjected to both static and fatigue loads. Working within the premise of ply-elasticity, a new concept of effective flaws is introduced which replaces the conventional constant ply strength criterion. Thus, the model consists of an application of fracture mechanics and a rational representation of material flaw distributions. Simulation examples are presented on [0 2 /90 2 ] s and [0 2 /90 3 ] s g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(42 citation statements)
references
References 4 publications
0
42
0
Order By: Relevance
“…A The simulation performed in this study differed from those of other studies, such as Wang's [27]. Instead of assuming a flaw size distribution in the transverse layer, we simulated the crack multiplication by partitioning the initial gage length into 5000 equal elements and assigning a strength value to each element in accordance with our experimental distribution function.…”
Section: Transverse Cracking -Statistical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A The simulation performed in this study differed from those of other studies, such as Wang's [27]. Instead of assuming a flaw size distribution in the transverse layer, we simulated the crack multiplication by partitioning the initial gage length into 5000 equal elements and assigning a strength value to each element in accordance with our experimental distribution function.…”
Section: Transverse Cracking -Statistical Modelmentioning
confidence: 99%
“…They also pointed out that if the matrix is completely homogeneous in strength, the cracks will always form at the midpoint of the segments. In this case, they can determine the probability density function (PDF) of crack spacing, which is f(/,/ 0 ) = / 0 /r (27) where l 0 is the crack spacing corresponding to a specific applied stress a x .…”
Section: Transverse Cracking -Statistical Modelmentioning
confidence: 99%
“…The interaction of transverse cracking, cracks which initiate randomly at matrix voids, and delamination causes quite an irregular fracture surface (i.e. delamination) and follows a completely random path that is contained by the two interfaces of the 90°-layer [39][40][41][42][43][44][45]. The delamination itself progresses abruptly and intermittently [39][40] with increasing load, although it might not extend across the specimen's width [40].…”
Section: 4mentioning
confidence: 99%
“…Similar observations were reported in [43], where this relationship is attributed to the constraining effect of the neighboring 00 layers. The transverse ply cracking strain is also affected by the thickness of the [ 0 4/ 9 0 8/ 0 4]T and may decrease from 0.0065 to 0.003 for [04/90n/04]T and [ 0 4/ 9 0 8/04]T, respectively, graphite/epoxy laminates [42]. It was concluded that "it is the total strain energy trapped in the 90*-layer which determines the onset of cracking, not the in-situ tensile stress" [44].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation